2022
DOI: 10.1002/dad2.12381
|View full text |Cite
|
Sign up to set email alerts
|

Associations between diffusion MRI microstructure and cerebrospinal fluid markers of Alzheimer's disease pathology and neurodegeneration along the Alzheimer's disease continuum

Abstract: Introduction White matter (WM) degeneration is a critical component of early Alzheimer's disease (AD) pathophysiology. Diffusion‐weighted imaging (DWI) models, including diffusion tensor imaging (DTI), neurite orientation dispersion and density imaging (NODDI), and mean apparent propagator MRI (MAP‐MRI), have the potential to identify early neurodegenerative WM changes associated with AD. Methods We imaged 213 (198 cognitively unimpaired) aging adults with DWI and used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…However, our findings are similar to a study on MAP-MRI in hemodialysis patients ( 22 ). Supporting this, research on Alzheimer’s disease has indicated that a decreased NG value could be indicative of axonal loss and demyelination ( 31 ). Changes in axial (NGAx) and radial (NGRad) neurite density also indicate changes in NG ( 11 ).…”
Section: Discussionmentioning
confidence: 94%
“…However, our findings are similar to a study on MAP-MRI in hemodialysis patients ( 22 ). Supporting this, research on Alzheimer’s disease has indicated that a decreased NG value could be indicative of axonal loss and demyelination ( 31 ). Changes in axial (NGAx) and radial (NGRad) neurite density also indicate changes in NG ( 11 ).…”
Section: Discussionmentioning
confidence: 94%
“…In mild cognitive impairment, increased RD and MD, but not AxD, were found to be associated with low cognitive performance ( 81 , 82 ), representing a diffusion profile more suggestive of demyelination ( 83 ) and neurodegeneration ( 84 ). Prior research has shown a nonmonotonic trajectory of diffusion metrics in early AD, suggestive of an early inflammatory process followed by a neurodegenerative process ( 69–71 ).…”
Section: Discussionmentioning
confidence: 98%
“…These approaches include bi-tensor free water models (such as Pasternak) and three-compartment models (such as neurite orientation dispersion and density imaging, NODDI). Markedly elevated free water levels have been associated with Parkinson's disease progression, multiple sclerosis degeneration and biomarkers of Alzheimer's disease [49][50][51]. Finally, WMH are seen in T2 fluid-attenuated inversion recovery (FLAIR) MRI and are considered to be representative of white matter gliosis and degeneration [52].…”
Section: Astrocyte Aqp4 Channels and Extracellular Free Watermentioning
confidence: 99%